A programmable origami-inspired space deployable structure with curved surfaces. (1st April 2022) - Wang, Chunlong; Guo, Hongwei; Liu, Rongqiang; Deng, Zongquan
Highlights: A novel space deployable structure with curved surface by employing the origami design concept is proposed. Programmability and kinematic performance of the thick-panel origami network are illustrated. A comprehensive quantitative design method to achieve a specific deployable status is established. Two sample prototypes of a circular cylindrical antenna and a parabolic antenna are manufactured to verify the design concept and exhibit potential applications. Abstract: Space deployable structures are widely used in multiple space missions, and origami-inspired design is becoming a prevalent method to create deployable structures with innovative folding concepts. This paper proposed a novel space deployable structure with curved surface by employing the origami design, which is generated by strategically integrating two types of plane-symmetric thick-panel origami modules and the formation of network is described in detail. By taking advantage of the kinematic programmability, this origami-based deployable structure can be utilized to construct different target configurations, such as circular cylindrical surface and parabolic surface. Geometric analysis of the origami-inspired deployable structure are provided, as well as a comprehensive quantitative design method to customize a specific deployable status. Furthermore, two sample prototypes of a circular cylindrical antenna and a parabolic antenna are manufactured to verify and exhibit the potential applications of the origami-based deployable structures. This study provides a new approach to construct space deployable structures with different curved surfaces for aerospace engineering applications.